Aktywność rynków ubezpieczeniowych w Japonii i Australii - Bożek-Węglarz, Sylwia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
This article consists of two main parts: comparison financial activity insurance market in Japan and Australia by the following indicators - market share in the OECD (direct gross premiums basis), density and penetration of insurance industry, retention ratio and also data related to major trends of insurance investments (selected data of technical activity of insurance companies in Japan). Density of insurance as indicator represents the average insurance spending per capita and has shown dominant position Japan among aggregated OECD and EU countries 'in total insurance. Ratio of penetration represents the relative importance of the insurance industry in the domestic economy and has shown Japan as one on the middle-sized markets of the worldwide insurance. In Australia level of the ratio of penetration in life insurance was significant in 2001. In general, important insurance activity indicators reflect the most significant characteristics of the insurance markets. In Japan and Australia insurance companies have invested most often in bonds and shares. Summing up, it should be said the development of insurance market is closely correlated with the activity of business written (especially gross written premiums) and efficiency of the policy investment in the country (e.g. Japan, Australia). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 55-63